Occupational stress in the ED: a systematic literature review. Issue 7 (11th October 2016) - Basu, Subhashis; Qayyum, Hasan; Mason, Suzanne
Abstract : Introduction: Occupational stress is a major modern health and safety challenges. While the ED is known to be a high-pressure environment, the specific organisational stressors which affect ED staff have not been established. Methods: We conducted a systematic review of literature examining the sources of organisational stress in the ED, their link to adverse health outcomes and interventions designed to address them. A narrative review of contextual factors that may contribute to occupational stress was also performed. All articles written in English, French or Spanish were eligible for conclusion. Study quality was graded using a modified version of the Newcastle-Ottawa Scale. Results: Twenty-five full-text articles were eligible for inclusion in our systematic review. Most were of moderate quality, with two low-quality and two high-quality studies, respectively. While high demand and low job control were commonly featured, other studies demonstrated the role of insufficient support at work, effort–reward imbalance and organisational injustice in the development of adverse health and occupational outcomes. We found only one intervention in a peer-reviewed journal evaluating a stress reduction programme in ED staff. Conclusions: Our review provides a guide to developing interventions that target the origins of stress in the ED. It suggests that those which reduce demand and increase workers' control over their job, improve managerial support, establish better working relationships and make workers' feel more valued for their efforts could be beneficial. We have detailed examples of successful interventions from other fields which may be applicable to this setting.